Fluorescent carbon nanodots for targeted in vitro cancer cell imaging - Aiyer, Sandhya; Prasad, Rajendra; Kumar, Manoj; Niryikar, K.; Jain, Bhanprakash; Kushwaha, Omkar S. (Applied Materials Today, 2016)
Carbon quantum dots (CQDs or C-dots, <= 10nm in size) are tiny carbon nanoparticles being envisaged in biosensing, bio-imaging and biomolecular/drug delivery. In the present investigation, green fluorescent carbon quantum/nano dots (GCQDs, similar to 3 nm in size) were synthesized through facile chemical slicing method. Further, folic acid (FA) functionalized GCQDs (GCQDs-FA) were obtained to enhance their targeting ability. FA is known to positively influence the binding potential and penetration into the cancer cells because of high abundance of folate receptors (FR) on various cancer cell membranes. We report high biocompatibility, photoluminescence stability and excellent in vitro cancer cell cytoplasm and nucleus targeting performance of GCQDs-FA on MCF-7 breast cancer cells. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cancer cell bio-imaging; Carbon quantum/nano dots; Cell cytoplasm and nucleus targeting; Green fluorescence; Photoluminescence stability; Targeting ability

Fluorescent carbon nanodots for targeted in vitro cancer cell imaging (vol 4, pg 71, 2016) - Aiyer, Sandhya; Prasad, Rajendra; Kumar, Manoj; Nirvikar, K.; Jain, Bhanprakash; Kushwaha, Omkar S. (Applied Materials Today, 2019)

Francisella novicida Cas9 interrogates genomic DNA with very high specificity and can be used for mammalian genome editing - Acharya, Sundaram; Mishra, Arpit; Paul, Deepanjan; Ansari, Asgar Hussain; Azhar, Mohd; Kumar, Manoj; Rauthan, Riya; Sharma, Namrata; Aich, Meghali; Sinha, Dipanjali; Sharma, Saumya; Jain, Shivani; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Genome editing using the CRISPR/Cas9 system has been used to make precise heritable changes in the DNA of organisms. Although the widely used Streptococcus pyogenes Cas9 (SpCas9) and its engineered variants have been efficiently harnessed for numerous gene-editing applications across different platforms, concerns remain regarding their putative off-targeting at multiple loci across the genome. Here we report that Francisella novicida Cas9 (FnCas9) shows a very high specificity of binding to its intended targets and negligible binding to off-target loci. The specificity is determined by its minimal binding affinity with DNA when mismatches to the target single-guide RNA (sgRNA) are present in the sgRNA:DNA heteroduplex. FnCas9 produces staggered cleavage, higher homology-directed repair rates, and very low nonspecific genome editing compared to SpCas9. We demonstrate FnCas9-mediated correction of the sickle cell mutation in patient-derived induced pluripotent stem cells and propose that it can be used for precise therapeutic genome editing for a wide variety of genetic disorders.
Keywords: CRISPR Cas9; gene therapy; Genome editing; iPSCs; sickle cell anemia

FnCas9-based CRISPR diagnostic for rapid and accurate detection of major SARS-CoV-2 variants on a paper strip - Kumar, Manoj; Gulati, Sneha; Ansari, Asgar H.; Phutela, Rhythm; Acharya, Sundaram; Azhar, Mohd; Murthy, Jayaram; Kathpalia, Poorti; Kanakan, Akshay; Maurya, Ranjeet; Vasudevan, Janani Srinivasa; Aparna, S.; et al. (eLife, 2021)
The COVID-19 pandemic originating in the Wuhan province of China in late 2019 has impacted global health, causing increased mortality among elderly patients and individuals with comorbid conditions. During the passage of the virus through affected populations, it has undergone mutations, some of which have recently been linked with increased viral load and prognostic complexities. Several of these variants are point mutations that are difficult to diagnose using the gold standard quantitative real-time PCR (qRT-PCR) method and necessitates widespread sequencing which is expensive, has long turn-around times, and requires high viral load for calling mutations accurately. Here, we repurpose the high specificity of Francisella novicida Cas9 (FnCas9) to identify mismatches in the target for developing a lateral flow assay that can be successfully adapted for the simultaneous detection of SARS-CoV-2 infection as well as for detecting point mutations in the sequence of the virus obtained from patient samples. We report the detection of the S gene mutation N501Y (present across multiple variant lineages of SARS-CoV-2) within an hour using lateral flow paper strip chemistry. The results were corroborated using deep sequencing on multiple wild-type (n = 37) and mutant (n = 22) virus infected patient samples with a sensitivity of 87% and specificity of 97%. The design principle can be rapidly adapted for other mutations (as shown also for E484K and T716I) highlighting the advantages of quick optimization and roll-out of CRISPR diagnostics (CRISPRDx) for disease surveillance even beyond COVID-19. This study was funded by Council for Scientific and Industrial Research, India.